2008
DOI: 10.4049/jimmunol.181.7.4452
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: The Mechanism of Invariant NKT Cell Responses to Viral Danger Signals

Abstract: Invariant NK T (iNKT) cells influence the response to viral infections, although the mechanisms are poorly defined. In this study we show that these innate-like lymphocytes secrete IFN-γ upon culture with CpG oligodeoxynucleotide-stimulated dendritic cells (DCs) from mouse bone marrow. This requires TLR9 signaling and IL-12 secretion by the activated DCs, but it does not require CD1d expression. iNKT cells also produce IFN-γ in response to mouse CMV infection. Their mechanism of mouse CMV detection is quite si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
158
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(169 citation statements)
references
References 22 publications
7
158
4
Order By: Relevance
“…Two recent studies showed that MCMV infection induces iNKT cells to become activated and to produce IFN-g, which in turn amplifies the NK cell response. iNKT-cell activation is CD1d-independent but requires type I interferons and IL-12 [33,34]. During viral infections, these cytokines might be produced by activated DC and can activate iNKT independent of CD1d presentation.…”
Section: Murine Cytomegalovirus (Mcmv)mentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies showed that MCMV infection induces iNKT cells to become activated and to produce IFN-g, which in turn amplifies the NK cell response. iNKT-cell activation is CD1d-independent but requires type I interferons and IL-12 [33,34]. During viral infections, these cytokines might be produced by activated DC and can activate iNKT independent of CD1d presentation.…”
Section: Murine Cytomegalovirus (Mcmv)mentioning
confidence: 99%
“…Importantly, activation pathways independent of CD1d allow iNKT cells to respond to diverse infectious agents including viruses. Indeed, iNKT cells can be activated via soluble factors released by TLR-activated DC such as type I IFN or IL-12 [33,34], or by co-stimulatory molecules like OX40/OX40L [53].…”
Section: Influenzamentioning
confidence: 99%
“…2,13,14 The second model proposes that V␣14iNKT cells are indirectly acti- vated (in the absence of foreign antigen for the TCR) by IL-12 and/or IL-18 secreted by TLR (4,7,8,9)-stimulated antigen-presenting cells. 13,27,28,51,52 Thus, TLRs serve a critical role in the initiation of innate immunity in microbes. 13,14,27,28 Although TLR7, TLR8, and TLR9 are vital for the recognition of viruses [23][24][25][26] and indirectly induce V␣14iNKT cell activation, 27,51,52 the potential role of TLR3, an innate immune receptor that is also typically involved in sensing viral danger signals in mediation of V␣14iNKT cell activation remains undefined.…”
Section: Discussionmentioning
confidence: 99%
“…13,27,28,51,52 Thus, TLRs serve a critical role in the initiation of innate immunity in microbes. 13,14,27,28 Although TLR7, TLR8, and TLR9 are vital for the recognition of viruses [23][24][25][26] and indirectly induce V␣14iNKT cell activation, 27,51,52 the potential role of TLR3, an innate immune receptor that is also typically involved in sensing viral danger signals in mediation of V␣14iNKT cell activation remains undefined. The results presented in this study demonstrate an important role for the TLR3 ligand, poly I:C, in promoting hepatic V␣14iNKT cell activation (without prior activation by exogenous viral administration).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation